Data, capacity-building, and training needs to address rural health inequities in the Northwest United States: a qualitative study. (17th April 2019) - Bekemeier, Betty; Park, Seungeun; Backonja, Uba; Ornelas, India; Turner, Anne M
Abstract: Objective: Rural public health system leaders struggle to access and use data for understanding local health inequities and to effectively allocate scarce resources to populations in need. This study sought to determine these rural public health system leaders' data access, capacity, and training needs. Materials and Methods: We conducted qualitative interviews across Alaska, Idaho, Oregon, and Washington with individuals expected to use population data for analysis or decision-making in rural communities. We used content analysis to identify themes. Results: We identified 2 broad themes: (1) challenges in accessing or using data to monitor and address health disparities and (2) needs for training in data use to address health inequities. Participants faced challenges accessing or using data to address rural disparities due to (a) limited availability or access to data, (b) data quality issues, (c) limited staff with expertise and resources for analyzing data, and (d) the diversity within rural jurisdictions. Participants also expressed opportunities for filling capacity gaps through training—particularly for displaying and communicating data. Discussion: Rural public health system leaders expressed data challenges, many of which can be aided by informatics solutions. These include interoperable, accessible, and usable tools that help capture, access, analyze, and display data to support health equity efforts in rural communities. Conclusion: Informatics has the potential to address some of the daunting data-related challenges faced by rural public health system leaders working to enhance health equity. Future research should focus on developing informatics solutions to support data access and use in rural communities.